An alternative approach to understanding doping behavior: A pilot study applying the Q-method to doping research. Issue 3 (June 2019) - Gatterer, K.; Niedermeier, M.; Streicher, B.; Kopp, M.; Schobersberger, W.; Blank, C.
Abstract: Background: Prevention plays an important role in the fight against doping. A lot of research in the field of doping and anti-doping has been conducted. Yet, there is still a lack of knowledge in understanding the various and multi-level impacting factors of doping behavior. Therefore, this paper aimed to apply the Q-method to doping research to identify items that potentially differentiate between athletes who dope and those who do not and to assess whether these items resemble constructs previously identified in socio-psychological literature to be predictive for doping intention, susceptibility, and behavior. As a secondary goal, we aimed to evaluate whether the Q-method method might be a suitable approach to doping prevention research. Methods: Five doped and five matched non-doped elite athletes from different sports were investigated. Each athlete completed three separate Q-sorts by indicating his/her degree of agreement with a total of 175 items on an 11-point Likert scale. Items stem from 13 different constructs such as attitudes towards doping, training/coach climate and moral disengagement. Results: Results showed that the Q-sorts clearly differentiate two types of athletes (non-doped and doped athletes). In total, only 15 (out of 175) items differentiated between the two groups, stemming from the constructs attitudes, sportspersonship, goal orientation and situational temptation/doping susceptibility. Conclusions: These results might be an initial indicator of items that differentiate between distinct types of athletes (doped and non-doped), and suggest that the Q-method might be a useful tool to differentiate these groups of athletes. However, further research to validate the items is needed before implementation into doping prevention strategies.